Agrobacterium-mediated transformation of banana Musa acuminata AA cv "âMas Lampungâ with hpt gene using sterile corm as target tissue - Nena, Ade; Witjaksono, Witjaksono; Estiati, Amy (ANNALES BOGORIENSES, 2009)
The protocol forÂ  Agrobacterium-mediated transformation of local banana plants cvÂ  âMas Lampungâ (AA) has been established. A selectable marker gene (hpt) has been used to study the transformation usingÂ  in vitro corm slices as target tissues.Â  BananaÂ  in vitro corm slices were co-cultivated with the EHA105 strain of Agrobacterium tumefaciens harbouring binary vector pCAMBIA 1301 containing hygromycin resistance gene (hpt) as a selectable marker and intron-containing Î²-Glucuronidase (gus-intron) gene as a reporter gene driven byÂ  CaMV 35S promoter.Â Â  Polymerase Chain Reaction (PCR) were used to examine the existence ofÂ  hpt gene in plants resulted from the transformation.Â  Using primer pairs specific for hpt gene, our PCR analysis on leaves showed the presence of theÂ  hptÂ Â  transgene in banana transgenic plants at first generation (T0) of transformation.Â  To prove the existence of hpt gene in the fruits of transgenic banana plants, PCR analysis were also carried out.Â  The data showed that theÂ  hptÂ  gene could be amplifiedÂ  from banana fruits of tested samples.Â Â  These result demonstrates that the Agrobacterium-mediated transformation method used in this experiment has been successful to transfer gene into banana plants. Thus, the transformation method reported here could be used as a standard protocol toÂ  transfer another useful genes into local banana plants cv. âMas Lampungâ.Â  Furthermore, the presence of transgene in fruits of banana transgenic plants is important achievementÂ  especially for transgene that is expected to be expressed in the fruit including to introduce vaccine genes into banana fruits for edible vaccine.Key words:Â  Agrobacterium,Â  hptÂ  gene, transgenic banana Mas Lampung, Musa acuminate corm slices, PCR